Relationships among microbiota, gastric cancer, and immunotherapy - Li, Yuzhen; Huang, Xiaona; Tong, Desheng; Jiang, Chenyu; Zhu, Xiaodan; Wei, Zhipeng; Gong, Tingjie; Jin, Chunhui (Frontiers in Microbiology, 2022)
Currently, conventional neoadjuvant therapy or postoperative adjuvant therapy, such as chemotherapy and radiation therapy, can only bring limited survival benefits to gastric cancer (GC). Median survival after palliative chemotherapy is also low, at about 8–10 months. Immunotargeting is a new option for the treatment of GC, but has not been widely replicated. The highly immunosuppressed tumor microenvironment (TME) discounts the efficacy of immunotherapy for GC. Therefore, new strategies are needed to enhance the immune response of the TME. This paper reviewed the relationship between microorganisms and GC, potential links between microorganisms and immunotherapy and research of microorganisms combined immunotherapy.